2017
DOI: 10.3390/rs9100971
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Influence of Crop Residue Burning on Local PM2.5 Concentrations in Heilongjiang Province Using Ground Observation and Remote Sensing Data

Abstract: Abstract:Although a many studies concerning crop residue burning have been conducted, the influence of crop residue burning on local PM 2.5 concentrations remains unclear. The number of crop residue burning spots was the highest in Heilongjiang province and we extracted crop residue burning spots for this region using MOD14A1 (Thermal Anomalies & Fire Daily L3 Global 1 km) data and national land cover data. By analyzing the temporal variation of crop residue burning and PM 2.5 concentrations in Heilongjiang pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…From a spatial perspective, the correlation in NEC is the strongest among the seven regions, especially in spring and autumn, suggesting that the PM concentration is closely related to crop residue burning in the burning-concentrated periods. This phenomenon was consistent with findings from previous studies suggesting that crop residue burning is related to PM 2.5 concentration [ 23 , 24 ]. The main reason for the poor correlation in NC is that the source of PM is high exhaust-emission of vehicles and industrial production, instead of crop residue burning [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…From a spatial perspective, the correlation in NEC is the strongest among the seven regions, especially in spring and autumn, suggesting that the PM concentration is closely related to crop residue burning in the burning-concentrated periods. This phenomenon was consistent with findings from previous studies suggesting that crop residue burning is related to PM 2.5 concentration [ 23 , 24 ]. The main reason for the poor correlation in NC is that the source of PM is high exhaust-emission of vehicles and industrial production, instead of crop residue burning [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…Given the potential risk PM exert on public health, it is essential to explore correlations between crop residue burning and PM concentrations. Yin et al revealed the spatial distribution of crop residue burning and PM 2.5 concentrations in China at a seasonal pattern [ 23 ], and Chen et al discussed the influence of crop residue burning on PM 2.5 concentration in Heilongjiang Province of China during a severe haze episode [ 24 ]. Zhuang et al analyzed the trend of crop residue burning in different regions of China from 2003 to 2017 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely agreed that ground monitoring can produce accurate results through field investigations. However, ground monitoring is impossible to generate massive temporally updated data with respect to PM 2.5 over large-scale areas due to a series of challenges involving high economic costs, a limited number of monitoring stations, and insufficient labour productivity [2], [3]. Satellite-based remote sensing monitoring can offset some limitations of traditional ground monitoring, which provides the capability to conveniently acquire data and an extensive monitoring range.…”
Section: Introductionmentioning
confidence: 99%